Annual abstract of statistics 1999 - Nigeria. Federal Office of Statistics (Lagos Federal Office Statistics, 1999)
It is compendium of important statistics analysis of socio-economic development at the national level.
sju 26/06/2019
Ref
Keywords: Statistics; Nigeria